Aerial Warfare: A Volatile Dialogue between the Plant Pathogen Verticillium longisporum and Its Antagonist Paenibacillus polymyxa - Rybakova, Daria; Rack-Wetzlinger, Ute; Cernava, Tomislav; Schaefer, Angelika; Schmuck, Maria; Berg, Gabriele (Frontiers in Plant Science, 2017)
Verticillium wilt caused by Verticillium spp. results in severe yield losses in a broad range of crops. Verticillium outbreaks are challenging to control, and exacerbated by increases in soil temperatures and drought associated with global warming. Employing natural antagonists as biocontrol agents offers a promising approach to addressing this challenge. Paenibacillus polymyxa Sb3-1 was proven to reduce the growth of V. longisporum during in vitro experiments and was shown to promote the growth of oilseed rape seedlings infested with V. longisporum. Our novel approach combined in vitro and in planta methods with the study of the mode of interaction between Sb3-1 and V. longisporum EVL43 via their volatile organic compounds (VOCs). Volatile and soluble substances, produced by both microorganisms as a reaction to one another’s VOCs, were detected by using both gas and liquid chromatography-mass spectrometry. P. polymyxa Sb3-1 continually produced antimicrobial and plant growth promoting VOCs, such as 2-nonanone and 3-hydroxy-2-butanone. Several other antimicrobial volatile substances, such as isoamyl acetate and durenol, were downregulated. The general metabolic activity of Sb3-1, including protein and DNA biotransformations, was upregulated upon contact with EVL43 VOCs. V. longisporum increased its production of antimicrobial substances, such as 1-butanol, and downregulated its metabolic activities upon exposure to Sb3-1 VOCs. Additionally, several stress response substances such as arabitol and protein breakdown products (e.g. L-Isoleucyl-L-glutamic acid), were increased in the co-incubated samples. The results obtained depict an ongoing dialogue between these microorganisms resulting in growth inhibition, the slowing down of metabolism, and the cell death of V. longisporum due to contact with the P. polymyxa Sb3-1 VOCs. Moreover, the results indicate that VOCs make a substantial contribution to the interaction between pathogens and their natural antagonists and have the potential to control pathogens in a novel, environmentally friendly manner.